Employees' experience of job satisfaction within a successful organisation - Milne, Claire (Rhodes University, Faculty of Humanities, Department of Psychology)
In the present organisational climate characterised by intense competition, the success of an organisation is increasingly dependent on its employees' expertise and knowledge (Carrel, Elbert, Hatfield, Grobler, Marx & Van der Schyf, 1997). Employees need to be motivated to contribute to the organisation's goals, for their knowledge and expertise to benefit an organisation (Lawler III, 1994). Organisations need to foster a situation in which employees have a positive attitude towards work and are able to benefit personally through directing their effort towards organisational goals. (Robbins, 2000) This study focuses on an organisation that has managed to link job satisfaction with organisational gain, and explores the link between these two subjects. A case study of a South African mining operation is reported on, and examined in-depth. The mine, a successful operation in terms of productivity, is recognised by its holding company as exemplary and is competing with the best base metal producers in the world. The research was conducted in two stages. The first stage consisted of 20 semi-structured individual interviews. Ten employees were selected from both the lower employee-levels and the higher employee-levels. The individual interviews focused on the experience of working at the mine with particular reference to interpersonal dynamics, job satisfaction, leadership style, and reward systems. During the second stage of the research, focus groups were conducted with two groups of seven employees each, one group from the lower-levels and one from the higher-levels. The focus groups aimed at obtaining a deeper understanding of the issues that emerged from the individual interviews. Grounded theory analysis was used during both the first, and second phase of the study. The results indicated that the mine's employees experience a high level fulfilment of higher-order needs, and that this experience is a reaction to the mine's performance enhancing culture. It is further shown that the same factors that create job satisfaction, when applied in excess, or in certain circumstances may lead to dissatisfaction within the same context.
Keywords: Employee motivation; Job satisfaction Employees -- Rating of; Performance standards; Management -- Employee participation; Organizational effectiveness; Organizational behavior; Employees -- Psychology; Wages -- Psychological aspects